Defect Engineering of van der Waals Solids for Electrocatalytic Hydrogen Evolution. Issue 22 (29th October 2020) - Yang, Leping; Yang, Xiaohan; Yu, Lingxiao; Lv, Ruitao
Abstract: Van der Waals solids with tunable band gaps and interfacial properties have been regarded as a class of promising active materials for electrocatalytic hydrogen evolution reaction (HER). However, due to the anisotropic features, their basal planes are usually electrochemically inert, only a few unsaturated edge atoms could serve as active centers to actuate H2 generation. Hence, material utilization and productivity efficiency are insufficient for practical applications. Recently, diverse defects have been confirmed to enable tailoring atomic configurations and electronic properties of van der Waals solids, thus triggering their superior catalytic activity of in‐plane atoms while introducing high amount of new active sites. In this minireview, we summarize the state‐of‐the‐art progress of defect engineering in van der Waals solids for HER, focusing in particular on their advantages in material modification and corresponding catalytic mechanisms. We also propose the challenges and perspectives of these catalytic materials in terms of both experimental synthesis and fundamental understanding of the defect structures. Abstract : Defect engineering in van der Waals solids plays an important role in triggering catalytic activity of their inert components for HER. It could efficiently modulate the chemical components and band‐gap states of van der Waals solids, thus impacting on the reactants capture, activation and release process. In this minireview, we summarize the latest advances of defect‐tailored van der Waals solids for HER. We focus on their advantages in material modification and corresponding catalytic mechanisms. The challenges and perspectives of defect‐tailored van der Waals solids towards HER are also proposed.